Analysis of Key Markets for Russian Weapons and Military Hardware in the BRICS Countries - DEGTEREVA, Ekaterina A.; MOSEIKIN, Yuri N.; CHERNOVA, Veronika Y. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
Nowadays economic and political development of BRICS is of high importance. The BRICS countries are getting more and more involved in cooperation with each other in all sectors including the military industry. The article analyses the current state of military-technological cooperation between Russia and its BRICS partners. The authors have studied major macroeconomic factors, examined the key financial mechanisms and schemes used today by various economies, and determined the military industry’s sectors with the greatest potential for each BRICS country. In the paper, the strengths and weaknesses of military-technical cooperation between Russia and other BRICS member states are assessed through a SWOT analysis. The medium-term prospects for this partnership are identified. The authors have concluded that the cooperation between Russia and BRICS in the military and technological sphere is promising, and even closer partnership is expected in the future.
Keywords: BRICS Alliance; defense; cooperation; armaments; Weapons Technology